"Street patrols of the Red Guard in Petrograd during the uprising of the Junkers [i.e. cadets]." From: 6/170 fol
"Street patrols of the Red Guard in Petrograd during the uprising of the Junkers [i.e. cadets]." From: 6/170 fol.